Predicting reconviction using the Psychological Inventory of Criminal Thinking Styles with English prisoners - Palmer, Emma J. (Legal and criminological psychology, 2004)
Purpose. The purpose of this study was to investigate the utility of the Psychological Inventory of Criminal Thinking Styles (PICTS) in predicting reconviction in a sample of male prisoners. Method. The PICTS was administered to 174 incarcerated male offenders at the point of their release from prison. Reconviction data were collected at a 2-year follow-up. Results. Of the eight PICTS scales, only superoptimism differed significantly between reconvicted and non-reconvicted prisoners, even when age and number of previous convictions were controlled for. Reconvicted offenders scored significantly higher on superoptimism, indicating a more criminal attitude. This finding was supported by a sequential logistic regression, where superoptimism contributed significant predictive power to predicting reconviction beyond a model containing age and number of previous convictions. Conclusions. The results are compared with previous research using the PICTS to predict release outcome. The utility of the PICTS as a predictor for release outcome is discussed.